Stock prices and monetary policy: Re-examining the issue in a New Keynesian model with endogenous investment - Michele Grossi; Roberto Tamborini (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
In this paper the authors present a New Keynesian quantitative model with endogenous investment and stock-market sector that may shed further light on two unsettled issues: whether central banks should include some financial indicator in their policy rules, and which indicator may be expected to generate better stabilization performance. For comparative purposes the authors replicate the policy framework and assessment strategy of the well-known no-inclusion model of BernankeGertler (Monetary Policy and Asset Price Volatility, 1999, and Should Central Banks Respond to Movements in Asset Prices? 2001). The performance of five policy rules is assessed. Two are traditional Taylor rules (i.e. with no financial indicators) that differ in the relative weight on the output and inflation gaps. Three are financial Taylor rules, that is, augmented with one financial indicator: the deviation from trend of stock prices, of Tobin's q (the rate of change stock prices relative to capital stock) and of investment. The authors show results that are at variance with BernankeGertler. First, because among the traditional rules the best performing one is output aggressive instead of inflation aggressive. Second, because the financial rule with Tobin's q outperforms the traditional inflation-aggressive one under all dimensions and cases. However, the authors cannot draw a univocal conclusion as regards the comparison between the financial rule with Tobin's q and the traditional but output aggressive rule.
Keywords: E5; E52; 330; New Keynesian models; monetary policy; stock markets and bubbles; Geldpolitik; Börsenkurs; Bubbles; Neukeynesianische Makroökonomik; Taylor-Regel; Tobin's Q; Theorie